Pourquoi aider les pays en développement ? Conceptions de la justice dans l’aide à l’adaptation au changement climatique - Romain Weikmans; Edwin Zaccai (Développement Durable et Territoires)
This article considers the moral grounds for financial transfers from developed countries to help developing countries adapt to the effects of climate change. We show that international adaptation finance is often seen as a matter of moral duty springing from some conceptions of justice. Indeed, financial flows for developing countries’ adaptation are often called for as rectification of the wrongs committed by developed countries given their disproportionate responsibility in the climate change problem. They are also – though sometimes implicitly – called for by some actors as a way of global wealth redistribution. We examine manifestations of these dimensions in the mandates of dedicated multilateral climate funds and in the assumptions made in the cost estimates of adaptation for developing countries. We show that most actors seem to be mainly driven by their material interests when it comes to referring to the moral justifications of their positions on international adaptation finance.